PERANCANGAN USER INTERFACE APLIKASI TOKO ONLINE “MORMO STORE” BERBASIS MOBILE APPLICATION - Rahmat Taufiq; dini faisal (Universitas Negeri Padang, 2020)
The design of the user interface page of the mobile application page of the online shop